2018
DOI: 10.1016/j.bja.2018.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Using an animated patient avatar to improve perception of vital sign information by anaesthesia professionals

Abstract: This study provides empirical evidence that an animated avatar offers the opportunity to transmit vital sign information significantly more quickly than conventional monitoring and with improved confidence and reduced cognitive effort. This could help care providers gain situation awareness more efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(107 citation statements)
references
References 34 publications
8
99
0
Order By: Relevance
“…The fact that the perceptive performance in the 30-s scenarios was not significantly different between the technologies suggests that avatar-based monitoring might be especially helpful when looking at monitors in short glances, which reflects the reality in clinical work [7,8,21]. The decreased size of the differences between avatar-based and conventional monitoring with increasing observation time, indicated by the smaller observed effect sizes in the 30-s scenarios, was similar to our previous studies, which investigated the effects of avatar-based monitoring for monitoring one patient at a time [23,25,26].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The fact that the perceptive performance in the 30-s scenarios was not significantly different between the technologies suggests that avatar-based monitoring might be especially helpful when looking at monitors in short glances, which reflects the reality in clinical work [7,8,21]. The decreased size of the differences between avatar-based and conventional monitoring with increasing observation time, indicated by the smaller observed effect sizes in the 30-s scenarios, was similar to our previous studies, which investigated the effects of avatar-based monitoring for monitoring one patient at a time [23,25,26].…”
Section: Discussionsupporting
confidence: 79%
“…In one study, a standardized distraction by a calculation task increased the workload measured by NASA TLX in both avatar-based and conventional patient monitoring [25]. Also, in a previous study with a comparable setting, we found shorter observation times to be associated with higher NASA TLX scores [23]. We collected data for this study using an iPad-based data collection tool [38].…”
Section: Study Proceduresmentioning
confidence: 88%
See 1 more Smart Citation
“…We divided the Visual Patient studies published so far into two major series: Visual Patient series 1 and Visual Patient series 2. Series 1 contains the preliminary studies, which aimed at qualitative and quantitative validation, stepwise improvement, and the first comparison of the technology's performance with regular monitoring [1][2][3]. In series 2, we tested the technology in three particular conditions for patient monitoring: using only peripheral vision [4], while being distracted [6], and when monitoring multiple patients at the same time, such as is in an intensive care unit central station monitor [5].…”
Section: Qualitative Review Of the Studies Conducted To Datementioning
confidence: 99%
“…In early 2020, we will begin a high-fidelity simulation study with a product by Philips (Koninklijke Philips N.V., Amsterdam, the Netherlands) developed from the Visual Patient concept. With this milestone, we move from basic research on our product [1][2][3][4][5][6][7] to clinical application research. This paper contributes a comprehensive overview of the research behind Visual Patient to the current literature.…”
Section: Introductionmentioning
confidence: 99%